2009
DOI: 10.14214/sf.179
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of silver birch pruning wounds to infection by white-rot fungus (Chondrostereum purpureum), a potential bioherbicide

Abstract: We artificially inoculated pruning wounds of silver birch (Betula pendula Roth) to study seasonal variation in their vulnerability to infection by the fungal decomposer Chondrostereum purpureum (Pers. ex Fr.) Pouzar. This information is critical to the assessment of incidental infection risks in areas where C. purpureum may be used as a bioherbicide. On seven monthly occasions between April and October 2005, 30 birch trees were pruned to yield a total of 210 experimental trees. On each occasion, 10 tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Furthermore, to observe wood necrotic symptoms the plant has to be destroyed. In addition, wood staining is not always caused by C. purpureum and it may also be produced by defense mechanisms of the plant or other pathogens (Vartiamäki et al 2009). Isolation and incubation is the traditional diagnosis method for wood pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, to observe wood necrotic symptoms the plant has to be destroyed. In addition, wood staining is not always caused by C. purpureum and it may also be produced by defense mechanisms of the plant or other pathogens (Vartiamäki et al 2009). Isolation and incubation is the traditional diagnosis method for wood pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Pouzar is an important wound pathogen that causes silverleaf disease in more than 230 woody species, including major fruit crops such as peach, plum, cherry, blueberry, apple, and also ornamental and forest crops (Bus et al 1996;Ogawa et al 2000;Setliff 2002;Spiers and Brewster 1997;Spiers and Hopcroft 1988). This basidiomycete fungus disseminates through airborne spores from different inoculum sources such as infected fruit orchards, windblown trees, logged areas, woodpiles, and pruned branches (De Jong et al 1990;Vartiamäki et al 2009), reaches wounded wood, like grafts and pruning cuts, and causes infection. Basidiospores germinate and mate with compatible hyphae forming heterokaryotic mycelia that grow deeper into the wood, producing the enzyme that causes the disease foliar symptoms.…”
mentioning
confidence: 99%
“…Considering the biocontrol use of C. purpureum, the first problem might be the infection of nontarget trees due to the increased production of basidiospores. This possibility was studied in North America by Wall (1991) and in Europe by de Jong et al (1990a, b) and Vartiamäki et al (2009b). All these studies suggested that the risk is small, and even the assumption of considerably increased spore load compared to natural levels may be incorrect (de Jong et al 1996).…”
Section: Potential Risksmentioning
confidence: 99%
“…Vartiamäki et al (2009b) tested this risk by pruning and inoculating birches in one month intervals from spring to autumn, and showed that pruning causes highest risk for C. purpureum infection in early spring. However, the infection in neighboring trees in control plots was very low throughout the experiment.…”
Section: Biosafety Aspectsmentioning
confidence: 99%